STANDARDIZING BEAUTY THROUGH ADVERTISING: A CRITICAL DISCOURSE ANALYSIS OF GARNIER LIGHT COMPLETE SERUM CREAM – CHELSEA ISLAN EDITION - Septiani, Resty Maudina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Garnier is one of the most famous international beauty products among women in Indonesia. Founded in France, Garnier is specialized in beauty products such as hair care, skincare, and hair color products. Among all the skincare products, Garnier Light Complete Serum Cream is one of the top sales in Indonesia. This paper is intended to analyze beauty product advertisements from Critical Discourse Analysis (CDA) perspective. This study applied qualitative research by using purposive sampling. Garnier’s advertisement does not only convince customers to buy their products but also plant their standard of beauty on women. The advertisement also standardizes the real beauty. The primary data were taken from the advertisement of Garnier Light Complete Serum Cream of Chelsea Islan Edition. This analysis is based on Fairclough’s 3-dimensional model of discourse. Fairclough’s 3-dimensional model discourse focuses on the standardization of real beauty of women through Garnier advertisement. The results show that the advertisements standardize the real beauty of women by using several linguistic devices, semiotics, and strategies. At the end, the Garnier advertisement establishes their ideology of “real beauty” in society.